Genetic engineering and bacterial pathogenesis against the vectorial capacity of mosquitoes. (October 2020) - Qasim, Muhammad; Xiao, Huamei; He, Kang; Omar, Mohamed A.A.; Liu, Feiling; Ahmed, Sohail; Li, Fei
Abstract: Mosquitoes are the main vector of multiple diseases worldwide and transmit viral (malaria, chikungunya, encephalitis, yellow fever, as well as dengue fever), as well as bacterial diseases (tularemia). To manage the outbreak of mosquito populations, various management programs include the application of chemicals, followed by biological and genetic control. Here we aimed to focus on the role of bacterial pathogenesis and molecular tactics for the management of mosquitoes and their vectorial capacity. Bacterial pathogenesis and molecular manipulations have a substantial impact on the biology of mosquitoes, and both strategies change the gene expression and regulation of disease vectors. The strategy for genetic modification is also proved to be excellent for the management of mosquitoes, which halt the development of population via incompatibility of different sex. Therefore, the purpose of the present discussion is to illustrate the impact of both approaches against the vectorial capacity of mosquitoes. Moreover, it could be helpful to understand the relationship of insect-pathogen and to manage various insect vectors as well as diseases. Highlights: Mosquitoes are vectors of viral and bacterial diseases. Vactor-pathogen association is influenced by biotic and abiotic factors. Bacterial pathogens produce toxins to destroy the vectorial capacity of target host. Mosquito molecular alteration decreases the vectorial capacity of vector. Small RNAs play a significant role in the gene expression and regulation.